Expand menu menu_open Minimize Start chapters Home History history History expand_more
{{ item.displayTitle }}
navigate_next
No history yet!
Progress & Statistics equalizer Progress expand_more
Student
navigate_next
Teacher
navigate_next
{{ filterOption.label }}
{{ item.displayTitle }}
{{ item.subject.displayTitle }}
arrow_forward
No results
{{ searchError }}
search
menu_open
{{ courseTrack.displayTitle }}
{{ statistics.percent }}% Sign in to view progress
{{ printedBook.courseTrack.name }} {{ printedBook.name }}
search Use offline Tools apps
Login account_circle menu_open

Solving Rational Equations

Solving Rational Equations 1.17 - Solution

arrow_back Return to Solving Rational Equations

For the given function, we will first draw its graph and then use the Horizontal Line Test to determine whether the inverse is a function. Then, we will find the inverse. Let's start!

Is the Inverse a Function?

To graph the given function, we should first determine its asymptotes. To do so, we will begin by rewriting the function rule to a single fraction. f(x)=1x47f(x)=-7x4+1x4\begin{gathered} f(x)=\dfrac{1}{x^4}-7 \quad \Leftrightarrow \quad f(x)=\dfrac{\text{-}7x^4+1}{x^4} \end{gathered} Recall that division by zero is not defined. Therefore, the rational function is undefined where x4=0.x^4=0. x4=0x=0\begin{gathered} x^4=0 \quad \Leftrightarrow \quad x=0 \end{gathered} The above means that x=0x=0 is the vertical asymptote of the function. To find the horizontal asymptote, let's pay close attention to the degrees of the numerator and denominator. f(x)=-7x4+1x4\begin{gathered} f(x)=\dfrac{\text{-}7x^{\color{#FF0000}{4}}+1}{x^{\color{#FF0000}{4}}} \end{gathered} We see that the degrees of the numerator and denominator are the same. Therefore, the horizontal asymptote is found by calculating the quotient between the leading coefficients. f(x)=-7x4+11x4\begin{gathered} f(x)=\dfrac{{\color{#FF0000}{\text{-}7}}x^4+1}{{\color{#FF0000}{1}}x^4} \end{gathered} Since -71=-7,\frac{\text{-}7}{1}=\text{-}7, there is a horizontal asymptote at y=-7.y=\text{-}7. Now, we will draw the asymptotes.

Next, we will make a table of values. We will include x-x\text{-}values to the left and to the right of the vertical asymptote.

xx 1x47\dfrac{1}{x^4}-7 f(x)f(x)
-4{\color{#0000FF}{\text{-}4}} 1(-4)47\dfrac{1}{({\color{#0000FF}{\text{-}4}})^4}-7 -6.99\approx{\color{#009600}{\text{-}6.99}}
-2{\color{#0000FF}{\text{-}2}} 1(-2)47\dfrac{1}{({\color{#0000FF}{\text{-}2}})^4}-7 -6.93\approx {\color{#009600}{\text{-}6.93}}
-1{\color{#0000FF}{\text{-}1}} 1(-1)47\dfrac{1}{({\color{#0000FF}{\text{-}1}})^4}-7 -6{\color{#009600}{\text{-}6}}
1{\color{#0000FF}{1}} 1147\dfrac{1}{{\color{#0000FF}{1}}^4}-7 -6{\color{#009600}{\text{-}6}}
2{\color{#0000FF}{2}} 1247\dfrac{1}{{\color{#0000FF}{2}}^4}-7 -6.93\approx {\color{#009600}{\text{-}6.93}}
4{\color{#0000FF}{4}} 1447\dfrac{1}{{\color{#0000FF}{4}}^4}-7 -6.99\approx {\color{#009600}{\text{-}6.99}}

Finally, let's plot and connect the points.

Now, we can apply the Horizontal Line Test.

We can see above that there are some horizontal lines that intersect the curve at more than one point. Therefore, the inverse of the given function is not a function.

Finding the Inverse

Before we can find the inverse of the given function, we need to replace f(x)f(x) with y.y. f(x)=1x47y=1x47\begin{gathered} f(x)=\dfrac{1}{x^4}-7\quad\Leftrightarrow\quad y=\dfrac{1}{x^4}-7 \end{gathered} Now, to algebraically determine the inverse of the given equation, we exchange xx and yy and solve for y.y. Given EquationInverse Equationy=1x47   x=1y47\begin{aligned} \underline{\textbf{Given Equation}}\quad&\quad\underline{\textbf{Inverse Equation}}\\ {\color{#0000FF}{y}}=\dfrac{1}{{\color{#009600}{x}}^4}-7\qquad\ &\qquad\ \ {\color{#009600}{x}}=\dfrac{1}{{\color{#0000FF}{y}}^4}-7 \end{aligned} The result of isolating yy in the new equation will be the inverse of the given function.
x=1y47x=\dfrac{1}{y^4}-7
Solve for yy
x+7=1y4x+7=\dfrac{1}{y^4}
y4(x+7)=1y^4(x+7)=1
y4=1x+7y^4=\dfrac{1}{x+7}
y=±1x+74y=\pm\sqrt[4]{\dfrac{1}{x+7}}
Finally, we write the inverse of the given function in function notation by replacing yy with f-1(x)f^{\text{-} 1}(x) in our new equation. f-1(x)=±1x+74\begin{gathered} f^{\text{-} 1}(x)=\pm\sqrt[4]{\dfrac{1}{x+7}} \end{gathered}